Site selection for vascular access creation in hemodialysis in end stage renal disease - Mahakalkar, Chandrashekhar C.; Kolte, Sanjay P.; Yeola, Meenakshi E.; Patwardhan, Maneesha A.; Jain, Niket N.; Kaple, Meghali N. (International Journal of Research in Medical Sciences, 2017)
Background: Chronic kidney failure is characterized with progressive and irreversible diminishing of glomerular filtration rate. AVF has been unanimously considered the gold standard vascular access of choice for hemodialysis. Arterio-venous fistula (AVF) for hemodialysis should be created in patients with endogenous creatinine clearance < 20 mL/min/1,73m2. Aim of current study was to choose the proper site for arteriovenous fistula creation with minimal complications. Methods: It was a prospective study, carried out in the dept. of surgery from April 2008 to August 2013. A total of 140 patients were studied over the period. The fistulae were created using radial artery cephalic vein side to side and brachial artery cephalic vein side to side or end to side anastomosis. Statistical analysis used: Mean, Standard deviation, Standard error. Results: A total 140 patients were studied, out of them 104 were males and 36 were females. The radiocephalic site was used for 82 (58.57%) patients and 58 (41.43%) patients were operated on brachiocephalic site. The mean inner diameter of radial artery, brachial artery and cephalic vein (intima to intima) at elbow and wrist were 21.49001 ± 0.901 (SE - 0.28492), 3.72533 ± 1.06837 (SE - 0.30841) and 0.68079 ± 0.49551 (SE - 0.116790) respectively. The mean flows velocity of brachial and radial artery were 76.10526 ± 4.54477 (SE - 1.04264) and 52.64286 ± 5.5968 (SE - 1.495810) respectively. The success rate of AV fistula on table was 97.85% (137 out of 140). The incidence of complication was 18.57%. Conclusion: The site for fistula creation depends on the quality of the artery and vein. To achieve good success rates preoperative color Doppler is essential to evaluate the vessels. The complication rates can be minimised by following standard operating protocols.